Intramuscular Pressure of Human Tibialis Anterior Muscle Reflects in vivo Muscular Activity - Ateş, Filiz; Davies, Brenda L.; Chopra, Swati; Coleman-Wood, Krista; Litchy, William; Kaufman, Kenton R. (Frontiers in Physiology, 2019)
Intramuscular pressure (IMP) is the fluid hydrostatic pressure generated within a muscle and reflects the mechanical forces produced by a muscle. By providing accurate quantification of interstitial fluid pressure, the measurement of IMP may be useful to detect changes in skeletal muscle function not identified with established techniques. However, the relationship between IMP and muscle activity has never been studied in vivo in healthy human muscles. To determine if IMP is able to evaluate electromechanical performance of muscles in vivo, we tested the following hypotheses on the human tibialis anterior (TA) muscle: (i) IMP increases in proportion to muscle activity as measured by electrical (Compound Muscle Action Potential (CMAP)) and mechanical (ankle torque) responses to activation by nerve stimulation and (ii) the onset delay of IMP (IMPD) is shorter than the ankle torque electromechanical delay (EMD). Twelve healthy adults (six females; mean (SD) = 28.1 (5.0) years old) were recruited. Ankle torque, TA IMP, and CMAP responses were collected during maximal stimulation of the fibular nerve at different intensity levels of electrical stimulation, and at different frequencies of supramaximal stimulation, i.e., at 2, 5, 10, and 20 Hz. The IMP response at different stimulation intensities was correlated with the CMAP amplitude (r2 = 0.94). The area of the IMP response at different stimulation intensities was also significantly correlated with the area of the CMAP (r2 = 0.93). Increasing stimulation intensity resulted in an increase of the IMP response (P < 0.001). Increasing stimulation frequency caused torque (P < 0.001) as well as the IMP (P < 0.001) to increase. The ankle torque EMD (median (interquartile range) = 41.8 (14.4) ms) was later than the IMPD (33.0 (23.6) ms). These findings support the hypotheses and suggest that IMP captures active mechanical properties of muscle in vivo and can be used to detect muscular changes due to drugs, diseases, or aging.